2021
DOI: 10.1111/acel.13459
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study of the frailty index highlights brain pathways in ageing

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
157
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 62 publications
1
157
0
Order By: Relevance
“…Furthermore, it also did not support the genetic causal links between FI and AD‐by‐proxy, a condition that shares strong genetic correlation with AD. By genetic risk score analysis, Atkins et al reported that AD may not influence frailty risk [15]. Therefore, the causal association between frailty and AD needs further investigation and more genetic variants, common pathways and shared risk factors related to the conditions need to be revealed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, it also did not support the genetic causal links between FI and AD‐by‐proxy, a condition that shares strong genetic correlation with AD. By genetic risk score analysis, Atkins et al reported that AD may not influence frailty risk [15]. Therefore, the causal association between frailty and AD needs further investigation and more genetic variants, common pathways and shared risk factors related to the conditions need to be revealed.…”
Section: Discussionmentioning
confidence: 99%
“…By genetic risk score analysis, Atkins et al reported that AD may not influence frailty risk [15]. Therefore, the causal association between frailty and AD needs further investigation and more genetic variants, common pathways and shared risk factors related to the conditions need to be revealed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study provides limited insight into the causal relationships between mental disorders and frailty in relation to mortality. However, it is likely that mental illness and frailty are mutually reinforcing, and may share common risk factors 50 . Finally, we cannot exclude the possibility of residual confounding, and other variables (e.g., genetics, healthcare access or drug prescriptions) not considered here may also affect the observed associations.…”
Section: Discussionmentioning
confidence: 99%